2011
DOI: 10.1309/ajcpz33mvmgzkewu
|View full text |Cite
|
Sign up to set email alerts
|

The Interobserver Reproducibility of Thyroid Fine-Needle Aspiration Using the UK Royal College of Pathologists’ Classification System

Abstract: The overall interobserver reproducibility of thyroid fine-needle aspiration (FNA) has not been comprehensively assessed. A blinded 6-rater interobserver reproducibility study was conducted of 200 thyroid FNA cases using the UK System, which is similar to The Bethesda System for Reporting Thyroid Cytology: Thy1, nondiagnostic; Thy2, nonneoplastic; Thy3a, atypia, probably benign; Thy3f, follicular lesion; Thy4, suspicious of malignancy; and Thy5, malignant. There was good interobserver agreement for the Thy1 (κ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 25 publications
1
87
1
Order By: Relevance
“…The same diagnostic system was also proposed as Thy3a in the recent UK Royal College of Pathologists' classification (UK system) [17,18,20,53,54]. The probability of malignancy (PTC type) was as high as 40-60% in indeterminate B, which may be exactly the same category as Thy3a in the UK system, and different from the AUS in the Bethesda system of the low-risk (5-15%) category [11,17,18,20,26,53,54,60]. Indeterminate B of the JTA system could be divided into two categories: AUS and suspicious for borderline and favor malignant (Table 1).…”
Section: Impact Of Risk Stratification Of Indeterminate Cytology Of Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The same diagnostic system was also proposed as Thy3a in the recent UK Royal College of Pathologists' classification (UK system) [17,18,20,53,54]. The probability of malignancy (PTC type) was as high as 40-60% in indeterminate B, which may be exactly the same category as Thy3a in the UK system, and different from the AUS in the Bethesda system of the low-risk (5-15%) category [11,17,18,20,26,53,54,60]. Indeterminate B of the JTA system could be divided into two categories: AUS and suspicious for borderline and favor malignant (Table 1).…”
Section: Impact Of Risk Stratification Of Indeterminate Cytology Of Fmentioning
confidence: 99%
“…3). Some researchers emphasized that PTC-type nuclear features in cytology were not associated with a low risk [4, [17][18][19][20] …”
Section: Impact Of Risk Stratification Of Indeterminate Cytology Of Fmentioning
confidence: 99%
“…FNA is used for estimating malignancy risk of the nodule to decide whether patient is a candidate for surgery or not (Cibas and Ali, 2009). Therefore, malignancy risk of each cytopathology result has been determined by different organizations to recommend best treatment options for each category (Cibas and Ali, 2009;Gharib et al, 2010;Kocjan et al, 2011). Additionally, these categorizations aim to decrease the rate of indeterminate results and provide a common language in between different disciplines, such as pathology, endocrinology and surgery.…”
Section: Introductionmentioning
confidence: 99%
“…These types of nodules are also defined as Thy3a category defined by The Royal College of Pathologists (TRCP) and as Class 3 (with suspicious follicular lesions also included) by the American Association of Clinical Endocrinologists/ Associazione Medici Endocrinologi/European Thyroid Association (AACE/AME/ETA) Task Force. Both guidelines recommend surgery to exclude malignancy unless the clinical, ultrasonographic, cytological and immunocytochemical features are considered favorable (Gharib et al, 2010;Kocjan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have considered the absence of suspicious US findings on follow-up to be an indicator of benignity, which may also explain the differences in percentages (Ho et al, 2014;Rosario, 2014;Yoo et al, 2015). Finally, some authors have reported a very poor inter-observer reproducibility for the Thy 3 category, in contrast to the good agreement seen for the other BTA categories (Kocjan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%